Wolbachia infections are virulent and inhibit the human malaria parasite Plasmodium falciparum in Anopheles gambiae. - Grant L Hughes (Public Library of Science (PLoS), 2011)
Endosymbiotic Wolbachia bacteria are potent modulators of pathogen infection and transmission in multiple naturally and artificially infected insect species, including important vectors of human pathogens. Anopheles mosquitoes are naturally uninfected with Wolbachia, and stable artificial infections have not yet succeeded in this genus. Recent techniques have enabled establishment of somatic Wolbachia infections in Anopheles. Here, we characterize somatic infections of two diverse Wolbachia strains (wMelPop and wAlbB) in Anopheles gambiae, the major vector of human malaria. After infection, wMelPop disseminates widely in the mosquito, infecting the fat body, head, sensory organs and other tissues but is notably absent from the midgut and ovaries. Wolbachia initially induces the mosquito immune system, coincident with initial clearing of the infection, but then suppresses expression of immune genes, coincident with Wolbachia replication in the mosquito. Both wMelPop and wAlbB significantly inhibit Plasmodium falciparum oocyst levels in the mosquito midgut. Although not virulent in non-bloodfed mosquitoes, wMelPop exhibits a novel phenotype and is extremely virulent for approximately 12-24 hours post-bloodmeal, after which surviving mosquitoes exhibit similar mortality trajectories to control mosquitoes. The data suggest that if stable transinfections act in a similar manner to somatic infections, Wolbachia could potentially be used as part of a strategy to control the Anopheles mosquitoes that transmit malaria.